Phytosociology and diametric structure of a fragment in the cerrado sensu stricto, south of tocantins - Santos, Mayronne Joaquim Fonseca dos; Andrade, Valdir Carlos Lima de; Freitas, Brenno Cunha; Ferreira, Rômulo Quirino de Souza; Bandeira, Sara Bezerra; Souza, Priscila Bezerra de (Scientia Agraria Paranaensis, 2017)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->The study was developed with the objective to analyze the phytosociology and diametric structure in a cerrado sensu stricto (Brazilian savannah) fragment with 7.5 ha located in the southern of Tocantins State, Brazil. Six plots of 20 x 10 m (200 m2) were allocated, and every shrub-tree individuals with circumference at breast height (CBH) larger than 9.5 cm were sampled. 486 individuals were registered, of which 476 are alive and 10 dead, distributed in 53 species, 50 genera and 29 families. The six most important species were Psidium catteleyanum, Astronium fraxinifolium, Tapirira guianensis, Qualea multiflora, Qualea grandiflora and Byrsonima stipulacea, totalizing 34.67% of the total IVI. The average height of the vegetation was 6.5 m and 7.6 cm for diameter, besides a basal area of 17.08 m2 ha-1, 4076 individuals per ha and volume of 83.53m3 ha-1. The diameter distribution of the fragment showed the typical pattern in inverted “J”.